Level of Social Stigma among Newly Divorced Women in the Light of Children and Work Variables - Al-Ziadat, Mariam A.; Al-Dalaeen, Anas S. (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aimed to identify the level of social stigma among recently divorced women in the past five years, considering the variables of children and employment. Method: To achieve the study's objectives, the psychometric properties' validity and reliability were verified by translating the Thornicroft, Brohan, Kassam, and Lewis (2008) scale. A sample of 145 recently divorced women in Karak Governorate was selected using the snowball sampling method. The study was conducted by sending a questionnaire link to the participants in 2022. Results: The study results showed a moderate level of social stigma among recently divorced women in Karak Governorate. Additionally, it was found that divorced women with children suffer from a higher level of social stigma compared to those without children. The results also showed that employed divorced women experience a lower level of social stigma compared to those who are unemployed. Conclusion: Based on the study results, it is recommended that society should pay more attention to recently divorced women to reduce the social stigma they face, especially those with children or those who are unemployed.